State Administrative Court Annulment Of Unlawful Demotions Through Fiqh Siyasah Jurisprudence: Pembatalan Penurunan Jabatan Pegawai Negeri Oleh Pengadilan Tata Usaha Melalui Fiqh Siyasah - Azan Mahriza Girsang; Zulham Zulham (Universitas Muhammadiyah Sidoarjo, 2026)
General Background The State Civil Apparatus plays a vital administrative role in government, requiring strict adherence to legal and ethical standards to ensure optimal public service delivery. Specific Background In Dairi Regency, a government employee faced an arbitrary demotion through Decree No. 400.7/000280 issued by the Head of the Health Office without proper procedural compliance. Knowledge Gap While previous studies have examined ethical violations by public officials, the specific intersection of procedural flaws in bureaucratic demotions and Islamic political principles remains underexplored. Aims This normative legal study examines the annulment of this demotion decree by the judiciary using both public administration and Islamic governance frameworks. Results The judiciary annulled the decree because the Head of the Health Office bypassed mandatory examination procedures, ignored the required examination team, and violated the overarching principles of good governance. Novelty This study integrates secular judicial decisions with the religious principle that public authority must inherently prioritize justice, transparency, and the public interest over unilateral bureaucratic discipline. Implications The findings mandate that government agencies must rigorously observe procedural justice and Islamic governance principles to guarantee legal protection for employees against arbitrary sanctions. Highlights The Dairi Health Office Head bypassed mandatory examination protocols when penalizing a subordinate. The judiciary revoked Decree No. 400.7/000280 for violating good governance regulations and accountability. Islamic political principles dictate that leadership actions must guarantee justice and protect individual rights. Keywords State Civil Apparatus; Fiqh Siyasah; Administrative Court; Demotion Sanction; Good Governance